Learning and Processing Multiple Languages: The More the Easier?. Issue 1 (3rd November 2020) - Festman, Julia
Abstract: This review scrutinizes the evidence concerning the factors that affect the ease with which multilinguals learn additional languages. First, I focus on language learning experiences that could help multilinguals acquire new languages (e.g., consequences of exposure, use of prior knowledge, biliteracy). I then discuss how multilinguals manage multiple languages and struggle with language control problems. By finally shedding more light onto effects of learning on the brain and the ways it adapts to the higher processing demands when having to manage multiple languages, it becomes clear that the key to understanding learning and processing of multiple languages lies in understanding the adaptive and dynamic nature of the brain. Although the brain is striving for efficient processing, environmental influences, communicative demands and genetic predispositions influence the learning and processing of multiple languages. I therefore suggest five specific effects related to multilingualism which may ease subsequent learning of multiple languages. Abstract :